Comparison of two minimally invasive enilconazole perendoscopic infusion protocols for the treatment of canine sinonasal aspergillosis. (25th October 2018) - Vangrinsven, E.; Girod, M.; Goossens, D.; Desquilbet, L.; Clercx, C.; Billen, F.
Abstract : Objectives: To compare two minimally invasive enilconazole infusion protocols for the treatment of canine sinonasal aspergillosis and evaluate the importance of complete endoscopic debridement in determining first treatment success rate. Materials and Methods: Data for 48 dogs with confirmed sinonasal aspergillosis treated with endoscopic debridement followed by per‐endoscopic enilconazole infusion were collected. Twenty‐four dogs were treated according to the previously published 1‐hour infusion protocol and 24 dogs underwent a simplified 15‐minute infusion protocol. Completeness of debridement, evaluated as partial or complete at the end of the procedure and outcome after one or several treatments were assessed in all dogs. Multi‐variable analysis was performed to derive odds ratios and 95% confidence intervals. Results: The median duration of the simplified protocol – 92∙3 minutes (range 40 to 140) – was substantially shorter than the duration of the previous protocol – 201∙3 minutes (range 120 to 265). First treatment success rates were 58 and 62∙5% for the previous and simplified protocol, respectively. Overall treatment success rate was similar in both groups (96%). Complete debridement was associated with an improved first treatment success rate compared to partial debridement. Clinical Significance: The simplified protocol is a valid alternative approach to the treatment of sinonasal aspergillosis. Completeness of endoscopic debridement before infusion is an important step for the success of treatment in canine sinonasal aspergillosis.